2010
DOI: 10.1590/s1415-52732010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Práticas alimentares no primeiro ano de vida de filhos de adolescentes

Abstract: ObjetivoEstudar as práticas alimentares de menores de um ano, filhos de adolescentes, residentes no município de Volta Redonda (RJ). MétodosEstudo transversal com 1.014 crianças selecionadas aleatoriamente na Campanha de Multivacinação de 2006, com aplicação de questionário fechado (recordatório de 24h). Foram analisadas características das mães e de seus filhos. As prevalências de aleitamento materno, aleitamento materno exclusivo, aleitamento materno predominante, a oferta de outros leites, a alimentação no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
6
0
9
Order By: Relevance
“…The second set, which included multivariate regression models, aimed to control the possible effect that changes in maternal characteristics: age (< 20, 20-24, 25-29, 30-34 e ≥ 35 years), schooling (< 7, 8-10 e ≥ 11 years), primiparity (yes/no), and work (yes/no); might have on the estimated proportions. Such maternal characteristics were elected as possible confounding variables due to their association with feeding practices in children < 1 year, as described in other studies 13,16,17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…The second set, which included multivariate regression models, aimed to control the possible effect that changes in maternal characteristics: age (< 20, 20-24, 25-29, 30-34 e ≥ 35 years), schooling (< 7, 8-10 e ≥ 11 years), primiparity (yes/no), and work (yes/no); might have on the estimated proportions. Such maternal characteristics were elected as possible confounding variables due to their association with feeding practices in children < 1 year, as described in other studies 13,16,17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…For adolescents, the association of age with personal factors increases the risk of early weaning compared with adult women. (7) In addition, cultural habits and social norms, as well as difficulties in the first day after delivery and support received from family, especially from their mothers, influence the behavior of adolescents concerning breastfeeding. (7,8) Other factor that influences both beginning and maintenance of breastfeeding is maternal confidence in the ability of breastfeeding, which is constructed and maintained by personal support and situations experienced by the woman.…”
Section: Introductionmentioning
confidence: 99%
“…(7) In addition, cultural habits and social norms, as well as difficulties in the first day after delivery and support received from family, especially from their mothers, influence the behavior of adolescents concerning breastfeeding. (7,8) Other factor that influences both beginning and maintenance of breastfeeding is maternal confidence in the ability of breastfeeding, which is constructed and maintained by personal support and situations experienced by the woman. (9)(10)(11) Maternal confidence is also called breastfeeding self-efficacy, which is a changeable and easy to access variable by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Some authors appoint, however, that the association between personal factors and the condition of being an adolescent and having an intimate partner increases the risk of early weaning for the adolescents in comparison with the adult mothers. 12 On the other hand, there is a higher prevalence of starting breastfeeding among adult women, who are also more prone to breastfeeding longer than the adolescents. 10,[13][14][15][16] Among adults as well as adolescents, it is observed that some of the variables related to the duration of the breastfeeding, such as the perception of little milk, personal and professional support and the experiences lived involve the construction or maintenance of maternal trust in one's ability to cope with a complex situation, which is the case of maternal breastfeeding.…”
Section: Introductionmentioning
confidence: 99%